Government Internal Control System In Cash Expenditure At The Livestock Service North Lombok Regency - Nandyta Frismaya Putri (International Journal of Economics, Management and Accounting, 2024)
This study focuses on the analysis of public fund expenditure in the livestock sector in North Lombok Regency, with an emphasis on improving the government's internal control system. Using 2022 livestock data and cash expenditure data, this study evaluates the efficiency of the use of public funds, identifies risks and efforts to prevent misuse of funds, and highlights the importance of developing an effective internal control system. The results of this study illustrate the potential for improvement in the management of public funds, by maximizing its positive impact on the growth of the livestock sector and community welfare in North Lombok Regency. The findings of this study provide a basis for stakeholders to adopt improvements in the internal control system, maintain transparency, and increase efficiency in the management of public funds for the purpose of sustainable development of the livestock sector